REKONSTRUKSI NORMATIF ATTACHMENT STYLE ANXIOUS AVOIDANT DALAM PERNIKAHAN: ANALISIS HUKUM KELUARGA ISLAM BERBASIS MAQASID AL-SYA’RIAH - Rama Rifqi Fahreza Fahreza; Muhsan Syarafuddin (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to conduct a comprehensive normative-juridical analysis of anxious and avoidant attachment behaviors within marital relationships from the perspective of Islamic Family Law. The urgency of this research is grounded in the phenomenon of insecure attachment styles, which frequently serve as the root of systematic conflicts yet are often overlooked in legal considerations due to their non-physical nature and the difficulty of evidentiary proof. The research methodology employed is qualitative, utilizing a literature review, conceptual approach, and legal comparison. The results demonstrate a novel contribution through the reconstruction of insecure attachment styles as a juridical variable, representing a simultaneous accumulation of internal nusyūz (disobedience) and syiqāq (chronic discord). These behaviors are explicitly qualified as ḍarar ma’nawī (psychological harm), possessing an objective threshold defined by the criteria of masyaqqah (extraordinary hardship) and the disruption of household stability. These findings provide new legitimacy for judges to exercise legal intervention based on Supreme Court Circular (SEMA) No. 3 of 2023, allowing for judicial action without adhering to the formal six-month separation requirement to uphold the principle of ḥifẓ an-nafs (protection of the soul). In practical application, this research integrates empirical data regarding the negative correlation between insecure attachment and marital satisfaction with curative mediation mechanisms through the role of ḥakam (mediators) specialized in psychospiritual aspects. The integration of Quranic values and positive legal instruments aims to terminate destructive internal harm while ensuring legal certainty and the protection of human dignity within the institution of marriage in Indonesia.